An Analysis Of Eleventh-Grade Students’ Mathematical Problem-Solving Abilities In Contextual Circle Problems - Salwa Salwa; Nurina Hidayah; Anie Faye M. Aribuabo (Universitas Wiralodra, 2025)
The low ability of students in solving non-routine problems highlights the importance of examining their mathematical problem-solving abilities in contextual circle problems. Problem-solving ability refers to how individuals utilize their knowledge and skills to handle unfamiliar situations. These abilities are analyzed based on five indicators proposed by Krulik and Rudnick: read and think, explore and plan, select a strategy, find an answer, and reflect and extend. This study employed a descriptive qualitative method with data collected through written tests and semi-structured interviews. Data were analyzed using the Miles and Huberman model. The test instrument consisted of three contextual circle problems with different levels of guidance: complete guidance, brief guidance, and no guidance. The results show that students’ problem-solving abilities varied across each problem. In the first problem, most students from all categories were able to complete the task according to the indicators, although errors occurred in the calculation and reflection stages. In the second problem, one student in the moderate category showed a decline from the planning to the reflection stage, while students in the low category experienced a more significant drop. In the third problem, only students in the high category consistently showed good abilities, while moderate and low-category students struggled in nearly all stages. One student in the low category even made no attempt to solve the problem. Students’ problem-solving profiles are reflected through their successes and obstacles in carrying out the five problem-solving stages.